Low Malay Language as A Stimulant for Bahasa Indonesia Development - Novika Stri Wrihatni; Sutami, Hermina (International Journal of Culture and Art Studies, 2019)
Bahasa Indonesia, which is the national and official language in Indonesia, is the result of the development of the High Malay Language (High Malay) in Riau. As the language used in the literature published by Balai Pustaka, the High Malay is respected as a language that is higher; than other languages used by the people of the Archipelago in the period before Indonesian independence in 1945. One of the lower languages is Low Malay Language (Low Malay). Some literary works written in this language were printed by printing presses belonging to individuals consisting of indigenous and Chinese groups. The Low Malay style was used in writing romance to make the stories feel more alive. This language of conversation should be counted as one type of language that contributes to the Indonesian language. The range of its uses is vast. However, with the development of politics in Indonesia, the Low Malay is once again marginalized. The language now only lives in conversation, yet it remains alive and developed along with the development of the times and the many influences of foreign languages on Indonesian language.